2003
DOI: 10.1046/j.1471-0528.2003.02353.x
|View full text |Cite
|
Sign up to set email alerts
|

Does perineal suturing make a difference? The SUNS trial

Abstract: While acknowledging the small sample size, the results are nonetheless important, showing persistent evidence of poorer wound approximation in those women who had not been sutured. Practitioners need to review the present practices of not suturing perineal lacerations until research examining the longer term implications is undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 21 publications
5
33
1
4
Order By: Relevance
“…These findings suggest that experiencing any degree of perineal trauma is associated with a higher risk of experiencing depressive symptoms and that symptoms can be persistent for those with a 2nd degree or more severe tear. In contrast, the second study found no effect of sutured vs. unsutured 2nd degree tears on EPDS scores at 10 days and 6 weeks postpartum (Fleming et al., ). The differences in findings between the two studies may be due to differences in discomfort and healing.…”
Section: Resultsmentioning
confidence: 96%
“…These findings suggest that experiencing any degree of perineal trauma is associated with a higher risk of experiencing depressive symptoms and that symptoms can be persistent for those with a 2nd degree or more severe tear. In contrast, the second study found no effect of sutured vs. unsutured 2nd degree tears on EPDS scores at 10 days and 6 weeks postpartum (Fleming et al., ). The differences in findings between the two studies may be due to differences in discomfort and healing.…”
Section: Resultsmentioning
confidence: 96%
“…Non-suturing of second degree tears has persisted in UK midwifery practice, despite current recommendations for practice, based on a systematic review of the evidence, supporting suturing [4]. Two small randomised controlled trials compared suturing versus non-suturing of second-degree tears [19,20] although both lacked statistical power. Lundquist et al [19] randomised 80 primiparous women to be sutured or not sutured, collecting data on pain, discomfort and dyspareunia at 2 to 3 days, 8 days and 6 months after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed ‘small’ lacerations left unsutured healed as well as ones which were sutured, however the definition and measurement of healing was not clarified, nor was a definition of a ‘small’ laceration provided. Fleming et al [20] randomised 74 primparous women who sustained a first or second degree tear to be sutured (n = 33) or not sutured (n = 41). Perineal pain and wound healing were assessed at 1 and 10 days and six weeks postpartum, and postnatal depression assessed at 10 days and six weeks postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies were found that had examined differences in outcomes in women who had perineal lacerations sutured or not sutured 14–17 . Studies have shown disparities in findings with regard to healing of sutured and nonsutured trauma 14,17 .…”
Section: Introductionmentioning
confidence: 99%